Two-dimensional hierarchically porous carbon nanosheets for flexible aqueous supercapacitors with high volumetric capacitance. Issue 23 (4th June 2019) - Yao, Lei; Lin, Junsheng; Yang, Haitao; Wu, Qin; Wang, Dongrui; Li, Xiujuan; Deng, Libo; Zheng, Zijian
Abstract : Pyrolytic carbons derived from two sister resins (with different crosslinking degrees) show a 2D nanosheet structure with and without hierarchical pores on the 2D plane, respectively. 2D-HPC displays a high volumetric capacitance in a flexible aqueous supercapacitor. Abstract : Two-dimensional carbon nanomaterials can be assembled into a dense film and used for flexible supercapacitors, but the high packing density leads to restacking problems and poor volumetric capacitance. To address this challenge, we report two-dimensional hierarchically porous carbon (2D-HPC) consisting of micro-, meso-, and macro-pores on the 2D sheet, which shows superior capacitance and rate capability compared with a 2D carbon nanosheet consisting predominantly of micro-pores. A flexible supercapacitor fabricated with the 2D-HPC presents a high volumetric capacitance of 412 F cm −3, a high volumetric energy density of 9.2 mW h cm −3 and a power density of 120 mW cm −3 .